Adolescent late-onset riboflavin-responsive multiple acyl-CoA dehydrogenase deficiency manifesting with severe multi-organ failure: a case report - Zhao, Yunhua; Li, Zhichao; Cui, Lili; Chen, Jun; Zhong, Wangtao (Frontiers in Pediatrics, 2025)
BackgroundMultiple acyl-CoA dehydrogenase deficiency (MADD) is a rare autosomal recessive disorder characterized by dysfunctional acyl-CoA dehydrogenases, leading to lipid accumulation in various tissues, including skeletal muscles, liver, and cardiac muscles, etc. Late-onset MADD presents with progressive muscular symptoms (muscle weakness, atrophy, and myalgia) and even multisystem disorders (metabolic encephalopathy, dilated cardiomyopathy, liver failure, acute kidney injury, respiratory failure, and cardiac arrest). Over the past decade, only one case of childhood late-onset MADD with severe multi-organ failure has been reported.Case presentationWe report a 15-year-old girl with worsening muscle weakness, atrophy, myalgia, hepatic insufficiency, respiratory failure and even cardiac arrest. Laboratory tests showed significantly elevated levels of creatine kinase MB isoenzyme (CK-MB) and lactate dehydrogenase (LDH). A weakly positive serum small ubiquitin-like modifier 1 activating enzyme (SAE1) antibody suggested antibody-negative polymyositis (PM), but serum acylcarnitine analysis indicated increased concentrations of various acylcarnitines, while urine organic acids was normal. Muscle biopsy revealed significant lipid deposition within muscle fibers pointing to the diagnosis of lipid storage myopathy (LSM). Genetic testing identified a homozygous c.250G>A (p.Ala84Thr) mutation in electron transfer flavoprotein dehydrogenase (ETFDH), inherited from her parents. Although this pathogenic mutation is known in MADD, it has not been associated with adolescent late-onset MADD with severe multi-organ failure. After riboflavin supplementation, the patient regained mobility without ventilator support, with no recurrence of myopathic symptoms upon follow-up.ConclusionMADD is a rare but treatable disease and its diagnosis is challenging due to its high clinical heterogeneity. Therefore, based on clinical, biochemical and pathological findings, gene analysis is critical for accurate diagnosis and clinical intervention, as riboflavin supplementation has shown lifesaving therapeutic benefit even in adolescent late-onset MADD with severe multi-organ failure.